Timely Access to Priority Medicines in Europe. Issue 1 (2017) - Bosone, Enrico; Giuliani, Giovanni; Martone, Nicoletta; Ponzianelli, Anna; Viola, Valeria
Many tools have been developed in Europe to accelerate the access to and the availability of medicines. However, this is currently governed by the national Member State procedures for pricing and reimbursement. In many cases, this leads to procedures that often take many months or even years to be completed. This paper explores ways that would allow a more accelerated approach and thus enable a more efficient administrative procedure to be adopted. Therefore, this would favor the timely availability of medicines for severe diseases when an unmet medical need is present.